Valorization of exo-microbial fermented coconut endosperm waste by black soldier fly larvae for simultaneous biodiesel and protein productions - Wong, C.Y. (Academic Press Inc., 2020)
The conventional practice in enhancing the larvae growths is by co-digesting the low-cost organic wastes with palatable feeds for black soldier fly larvae (BSFL). In circumventing the co-digestion practice, this study focused the employment of exo-microbes in a form of bacterial consortium powder to modify coconut endosperm waste (CEW) via fermentation process in enhancing the palatability of BSFL to accumulate more larval lipid and protein. Accordingly, the optimum fermentation condition was attained by inoculating 0.5 wt of bacterial consortium powder into CEW for 14â21 days. The peaks of BSFL biomass gained and growth rate were initially attained whilst feeding the BSFL with optimum fermented CEW. These were primarily attributed by the lowest energy loss via metabolic cost, i.e., as high as 22 of ingested optimum fermented CEW was effectively bioconverted into BSFL biomass. The harvested BSFL biomass was then found containing about 40 wt of lipid, yielding 98 of fatty acid methyl esters of biodiesel upon transesterification. Subsequently, the protein content was also analyzed to be 0.32 mg, measured from 20 harvested BSFL with a corrected-chitin of approximately 8. Moreover, the waste reduction index which represents the BSFL valorization potentiality was recorded at 0.31 g/day 20 BSFL. The benefit of fermenting CEW was lastly unveiled, accentuating the presence of surplus acid-producing bacteria. Thus, it was propounded the carbohydrates in CEW were rapidly hydrolysed during fermentation, releasing substantial organic acids and other nutrients to incite the BSFL assimilation into lipid for biodiesel and protein productions simultaneously. Â© 2020 Elsevier Inc.